2007
DOI: 10.14507/epaa.v15n5.2007
|View full text |Cite
|
Sign up to set email alerts
|

Responding to the education reform agenda: A study of school superintendents' instructional leadership.

Abstract: Education reforms have affected schools and the educators who work in them. Using state-wide survey data from 1993 and 2003, this study examines how the work of school superintendents has been affected over a ten-year period by these reform initiatives, especially increased demands for accountability. The general message from our data is that superintendents are interested in curriculum and instruction and believe these are important tasks, but the daily realities of their work often subvert even the most comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 18 publications
1
33
0
3
Order By: Relevance
“…Several studies (Alsbury & Whitaker, 2007;Bjork, 1993;Candoli, 1995;Grogan, 2000) suggest focus on other roles within the position, such as organizational manager, policymaker, and political negotiator have dominated superintendents' agendas. These assumed roles reflect direct and/or indirect realities of a challenging and conflicting position that has resulted in time and energy obstacles to instructional leadership that daily overload the average superintendent (Bredeson & Kose, 2007;Glass et al, 2000).…”
Section: Superintendents' Instructional Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies (Alsbury & Whitaker, 2007;Bjork, 1993;Candoli, 1995;Grogan, 2000) suggest focus on other roles within the position, such as organizational manager, policymaker, and political negotiator have dominated superintendents' agendas. These assumed roles reflect direct and/or indirect realities of a challenging and conflicting position that has resulted in time and energy obstacles to instructional leadership that daily overload the average superintendent (Bredeson & Kose, 2007;Glass et al, 2000).…”
Section: Superintendents' Instructional Leadershipmentioning
confidence: 99%
“…They are expected more than ever before to be aware of the achievement of all groups of students as measured by standardized tests. (Sherman, 2008 p. 678) For many superintendents, the role of instructional leader has not been assumed even when practicing superintendents rank curriculum and instruction as top priorities (Bredeson & Kose, 2007;Myers, 1992). Superintendents in spite of recognizing the importance of their direct involvement in curriculum and instruction on student achievement actually spend little time in these areas (Bredeson & Johansson, 1998).…”
Section: Superintendents' Instructional Leadershipmentioning
confidence: 99%
“…The role of the superintendent has shifted from instructional leadership and helping teachers to teach better to one that responds to outside pressure and political influences from government regulation, financial issues and student accountability from legislation such as NCLB (Bredeson, 2007). Hurley (2001) points out that the number of students being serviced in special education programming has increased dramatically, accounting for an increasingly larger percentage of the school population, and the new regulations governing these students require more administrative time and effort to complete.…”
mentioning
confidence: 99%
“…Although each of these three areas has great merit and helps to improve the lives of millions of children, it is clear that they have also changed the face of school administration by adding more responsibility and pressure on those in leadership positions. As evidence of this, Bredeson (2007), who compared results of questionnaires and inter-views administered in 1994 and again in 2003, found that the work of superintendent has increased dramatically to the point of work overload that can hamper the effectiveness of the leader in this position. He also points out that superintendents often complain that with the increasing number of mandates, there is too much that needs to done and not enough time to do it.…”
mentioning
confidence: 99%
See 1 more Smart Citation